THE DANGERS OF POLITICAL MONEY FOR A CLEAN DEMOCRACY PROCESS UP TO ELECTIONS FOR VILLAGE HEADS, REGIONAL HEADS, LEGISLATIVE ELECTIONS AND GENERAL ELECTIONS IN INDONESIA - Junaedi, Junaedi; Hidayat, Rumanul; Yusuf, Anas (IJBLE Scientific Publications Community Inc., 2023)
Elections for Village Heads, Regional Heads, Legislative Elections and General Elections in Indonesia should be carried out without being coloured by political money fraud, because of the dangers of political money for a clean democratic process ahead of the election of village heads, regional heads, legislative elections and general elections in Indonesia 2024, to achieve that power and victory, they used all kinds of methods. And that power will later be used to recover losses due to money politics. For this reason, Money Politics is considered a serious crime in the world of politics that must be fought and eliminated together. Money politics is the biggest enemy of democracy and is a 'bogey' that is familiar with holding elections in Indonesia. In the implementation of post-reform elections, money politics is a violation that is always in the spotlight. Uniquely, both election participants and the public are both involved in money politics circles. To fight the practice of Political Money Towards the Election of Village Heads, Regional Heads, Legislative Elections and General Elections in Indonesia 2024, the role of true politicians is needed who truly understand that the meaning of politics is the art of managing the country and its goal is to create the common good solely for people's welfare. Politics requires good people in it, who have a comparative advantage in the sense of having competence, and at the same time also have a competitive advantage. This is because goodness in politics needs to be fought for until it is transformed into state political policies. The Dangers of Political Money for a Clean Democratic Process Towards the Election of Village Heads, Regional Heads, Legislative Elections and General Elections in Indonesia 2024 will have long-term impacts, which will harm everyone (society), not only harm society as a whole, it can even harm the country, the nation, with various new problems that might occur due to the practice of this money politics. the impact of money politics can also damage the democratic order in a country, so that if it continues it will create new problems in society and even the state and can damage the mentality of the next generation which will have a labour impact on the welfare of society and the progress of a nation in the future. So that the practice of money politics must be stopped immediately because money politics demeans the people; Money Politics Is a Trap for the People; Money Politics Will Lead to Corruption; Money Politics Kills Society's Transformation.